Effect of Journal Misalignment on the Static Characteristics of Porous Journal Bearings Lubricated with Couple Stress Fluid - Lekaa' H. Abd Al-shaheed (Al-Khwarizmi College of Engineering – University of Baghdad, 2012)
In this paper, a theoretical study to the effect of journal misalignment on the static characteristics of oil filled porous journal bearing when lubricated with couple stress fluid has been carried out.